Nanosystems in Cosmetic Products: A Brief Overview of Functional, Market, Regulatory and Safety Concerns - Chiara Ferraris; Clara Rimicci; Sara Garelli; Elena Ugazio; Luigi Battaglia (MDPI AG, 2021)
Nanosystems exhibit various innovative physico-chemical properties as well as a range of cosmetic functions, including increased skin retention for loaded compounds. The worldwide nano-market has therefore been consistently extensive in recent decades. This review summarizes the most important properties of nanosystems that are employed in cosmetics, including composition, functions and interactions with skin, with particular attention being paid to marketed products. Moreover, the worldwide regulatory landscape of nanomaterials used as cosmetic ingredients is considered, and the main safety concerns are indicated. In general, advanced physico-chemical characterization is preliminarily needed to assess the safety of nanomaterials for human health and the environment. However, there is currently a shortfall in global legislation as a universally accepted and unambiguous definition of a nanomaterial is still lacking. Therefore, each country follows its own regulations. Anyhow, the main safety concerns arise from the European context, which is the most restrictive. Accordingly, the poor dermal permeation of nanomaterials generally limits their potential toxic effects, which should be mainly ascribed to unwanted or accidental exposure routes.